Audism and The International Classification of Functioning, Disability and Health Model in CODA Film - Wiralaksana, Muhammad Guntur (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2024)
Injustices in the form of discrimination are experienced frequently in the workplace by oppressed groups, including people with disabilities. Discrimination towards deaf people is audism, and it can spur from many groups or bodies, as well as Deaf people themselves. This research aims to elucidate whether there is disability or not in employment context in Leo and Frank characters from CODA film by Sian Heder, considering they are subjected to audism a lot in their work space. This research looks at CODA film by using the framework of audism and The International Classification of Functioning, Disability, and Health model by World Health Organization. This research uses qualitative methods to gather corresponding data from CODA film. The result shows that Deaf people are found a lot of times discriminated against by society. the ICF model shows that even though Frank and Leo are impaired, they become abled through certain circumstances such as a system that enables deaf workers and devices supporting their working tasks. This research indicates that negative stereotypes and misconceptions about Deaf individuals often lead to systemic barriers in hiring practices and workplace integration, resulting in underemployment and limited career advancement opportunities. Despite the growing visibility of Deaf representation in media, such as the film CODA, there is insufficient analysis of how these portrayals influence societal attitudes and employment prospects for Deaf individuals. This study aims to fill this gap by examining the representation of audism in CODA and its implications for the employment experiences of Deaf characters, thus contributing to a deeper understanding of the intersection between media representation and employment outcomes.